Computational intelligent data analysis for sustainable development - Yu, Ting 1975-; Chawla, Nitesh V.; Simoff, Simeon (Chapman & Hall/CRC data mining and knowledge discovery series, 2013)
"Intelligent data analysis techniques offer powerful solutions to collecting and analyzing vast quantities of environmental and economic data, which lead to better decision making for sustainable development. This volume is the first to discuss the treatment of intelligent data analysis techniques in sustainable development applications. The book describes the emerging use of data mining, machine learning, artificial neural networks, data visualization, knowledge discovery, GIS, and other technologies to tackle environmental, economic, and social issues, including climate change, risk management, and population growth"--Provided by publisher.